2010
DOI: 10.1128/aac.01417-09
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Molecular Markers of Drug Resistance in 2009 Pandemic Influenza A (H1N1) Viruses by Pyrosequencing

Abstract: The M2 blockers amantadine and rimantadine and the neuraminidase (NA) inhibitors (NAIs) oseltamivir and zanamivir are approved by the FDA for use for the control of influenza A virus infections. The 2009 pandemic influenza A (H1N1) viruses (H1N1pdm) are reassortants that acquired M and NA gene segments from a Eurasian adamantane-resistant swine influenza virus. NAI resistance in the H1N1pdm viruses has been rare, and its occurrence is mainly limited to oseltamivir-exposed patients. The pyrosequencing assay has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
121
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(124 citation statements)
references
References 38 publications
3
121
0
Order By: Relevance
“…While amino acid substitution 147GR in NA emerged in a recombinant laboratory strain and was only found in a small number of natural virus isolates [32], various amino acids are found at position 151 of NA in different influenza A(H3N2) viruses [33]. However, it was found that most substitutions from 151D to different amino acids were acquired upon propagation of viruses in the laboratory [18,[33][34][35][36] and that the majority of clinical samples that were not passaged in culture possessed 151D [33,36]. Here, we investigated the occurrence of the amino acids histidine and arginine at NA position 150 in all publicly available full-genome sequences of human A(H3N2) influenza viruses since the year 2000 and found an almost complete shift from histidine to arginine over the years, regardless of whether the sequences were derived from clinical specimens or passaged viruses.…”
Section: Discussionmentioning
confidence: 91%
“…While amino acid substitution 147GR in NA emerged in a recombinant laboratory strain and was only found in a small number of natural virus isolates [32], various amino acids are found at position 151 of NA in different influenza A(H3N2) viruses [33]. However, it was found that most substitutions from 151D to different amino acids were acquired upon propagation of viruses in the laboratory [18,[33][34][35][36] and that the majority of clinical samples that were not passaged in culture possessed 151D [33,36]. Here, we investigated the occurrence of the amino acids histidine and arginine at NA position 150 in all publicly available full-genome sequences of human A(H3N2) influenza viruses since the year 2000 and found an almost complete shift from histidine to arginine over the years, regardless of whether the sequences were derived from clinical specimens or passaged viruses.…”
Section: Discussionmentioning
confidence: 91%
“…Although powerful, this approach is limited by access to costly equipment and requires an external database (Abbott Molecular, Carlsbad, CA) for data analysis and interpretation. Conversely, pyrosequencing (Qiagen) has been utilized widely by surveillance laboratories in the United States and other countries, mainly for monitoring drug resistance among influenza viruses (26)(27)(28)(29)(30). Unlike drug resistance testing, which commonly requires the analysis of a single SNP, identification of six H3 clades presents a more challenging task.…”
Section: Discussionmentioning
confidence: 99%
“…Amino acid substitutions at position 223 in NA have previously been shown to affect virus susceptibility to both oseltamivir and zanamivir, in recent A(H1N1)pdm09 and seasonal viruses. 19,20 Residue 223 is located in the framework of the NA active site, and thus interacts with the catalytic residues to which antiviral drugs bind. 21 The contribution of V480I in PB2 to the reduced susceptibility profile observed is unclear.…”
Section: Discussionmentioning
confidence: 99%